2017
DOI: 10.1080/01495739.2017.1360165
|View full text |Cite
|
Sign up to set email alerts
|

Variable kinematic shell elements for composite laminates accounting for hygrothermal effects

Abstract: This paper presents advanced shell models for the steady state hygrothermal analysis of composite laminates. The Carrera Unified Formulation is used to derive refined models that include both Layer-Wise (LW) and Equivalent Single Layer (ESL) models. The governing equations are derived from the Principle of Virtual Displacement (PVD) taking into account thermal and hygroscopic effects. The geometrical relations for the exact cylindrical geometry are here considered. Through-the-thickness variations of temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…where i indexes the finite element nodes, F (•) is a thickness function similar to a Taylor series expansion. Cinefra et al [64] showed that thickness functions based on trigonometric sine, cosine and exponential series are also admissible to model higher-order shear deformation theories. As a second example, a displacement field based on a layer-wise approach can read…”
Section: Finite Element Methods With Carrera's Unified Formulationmentioning
confidence: 99%
“…where i indexes the finite element nodes, F (•) is a thickness function similar to a Taylor series expansion. Cinefra et al [64] showed that thickness functions based on trigonometric sine, cosine and exponential series are also admissible to model higher-order shear deformation theories. As a second example, a displacement field based on a layer-wise approach can read…”
Section: Finite Element Methods With Carrera's Unified Formulationmentioning
confidence: 99%
“…In this manuscript, the Carrera Unified Formulation (CUF) [ 26 ] is utilised for the numerical modelling of VSC plates to exploit its capabilities of creating structural models in which the desired accuracy of the solution is considered as input of the analysis, as demonstrated in [ 27 ]. CUF has been employed for a wide variety of problems such as rotor dynamics [ 28 ], hygrothermal analysis [ 29 ] and incompressible flow analysis [ 30 ]. Moreover, CUF has been recently extended to the study of VSC.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, the research activity has focused on the development of shell and plate models incorporating the effects mentioned above [9,10]. Most recent efforts describe well the open research topics and refinement techniques related to shells, such as, improvements of classical models [11] and higher-order models [12][13][14]; asymptotic approaches [15]; improvement of FE performances regarding membrane and shear locking [16][17][18][19][20][21], mesh accuracy [22], and distortion [23]; improved modeling of the interlaminar shear stresses [24]; Layer-Wise (LW) models [25,26]; Zig-Zag models [27,28]; mixed formulations [29][30][31]; variable kinematics finite elements with multifield effects [32]; extensions to non-linear problems [33,34] and peridynamics [35]; innovative solution schemes such as the numerical manifold method [36].…”
Section: Introductionmentioning
confidence: 99%